Sistem Pakar Untuk Mendeteksi Penyakit Infeksi Saluran Pernafasan dengan Metode Dempster Shafer di Kabupaten Pandeglang Provinsi Banten - Robby Rizky (Ikatan Ahli Informatika Indonesia, 2018)
Pandeglang regency is one of the districts that are left behind in Banten province in the field of pandeglang district technology one of the districts that are far from urban minimum health facility that support at the hospital of the nearest hospital hence the researcher want to research about the respiratory tract infection using DEMPSTER SHAFER method. Expert systems are systems that are designed and implemented with the help of a particular programming language to be able to resolve problems as do the experts. One application of expert system can be used to diagnose respiratory disease caused by Air conditioner (AC). Respiratory diseases are a group of complex and heterogeneous diseases caused by various causes and may affect any site along the respiratory tract Acute respiratory infection (ARI) is a severe infection of the sinuses, throat, airways or lungs. Infections that occur more often caused by viruses although bacteria can also cause respiratory function to be disrupted. If not treated promptly, ARDs may spread throughout the respiratory system.